Strategi Pengembangan Agribisnis Hortikultura di Luwu Utara: Suatu Pendekatan Kelembagaan dan Eko-Geografi - Nuddin, Andi; Jamil, Muh. Hatta; Laapo, Alimuddin (Journal Galung Tropika, 2021)
The North Luwu Regency Government has established a policy of developing horticultural agribusiness areas and strengthening the distance between the regional center and rural areas as producers of fruit and vegetable commodities. However, the support for the potential of natural resources is still a matter of debate between institutions. The purpose of the research was to describe the potential of eco-geographical resources and the level of importance of the institutional system in the development of horticultural agribusiness. The data that has been obtained were analyzed through two approaches, namely the data concerning the eco-geographical aspect which was analyzed through a regional complex approach. Meanwhile, data concerning social and institutional aspects were analyzed through the Interpretative Structural Modeling (ISM) approach. The results showed that all aspects of eco-geography including topography, marble level, soil type, and rainfall, were potential resources in horticultural development. Although all aspects other than the amount of funding, desperately need effective management. ISM analysis showed that horticulture development requires strategic program support, namely: (1) development of transportation facilities, (2) effectiveness of inter-institutional coordination, (3) program legitimacy and socialization, equal distribution of vision and mission of horticulture programs, (4) optimization of the role of institutions, (5) strengthening commitment between sectors, (6) increasing knowledge, and (7) developing strategic programs. Overall, the program will be easier to implement when it is supported by a strong institutional system.